1.Chứng minh rằng :
a) [TEX]sina sin(\frac{pi}{3} - a) sin (\frac{pi}{3} + a) = \frac{1}{4} sin3a[/TEX]
[TEX]VT = \sin a \sin(\frac{\pi}{3} - a) \sin (\frac{\pi}{3} + a) = \frac{1}{2}\sin a \left(- \cos \left(\frac{2\pi}{3} \right) + \cos \left( -2a \right) \right)[/TEX]
[TEX]=\frac{1}{2}\sin a \left(\frac{1}{2} + \cos \left( 2a \right) \right)[/TEX]
[TEX]=\frac{1}{2}\sin a \left(\frac{1}{2} + 1 - 2\sin ^ 2 (a) \right)[/TEX]
[TEX]=\frac{1}{4} \left( 3\ sin a - 4\sin ^ 3 (a) \right) = \frac{1}{4}\sin(3a) = VP[/TEX]
b)[TEX]cosa cos (\frac{pi}{3} - a) cos (\frac{pi}{3} + a) = \frac{1}{4} cos3a[/TEX]
Thế [TEX]a = b + \frac{\pi}{2}[/TEX] vào
câu a. Ta có:
[TEX]\sin \left( b + \frac{\pi}{2} \right) \sin(\frac{\pi}{3} - \left( b + \frac{\pi}{2} \right)) \sin (\frac{\pi}{3} + \left( b + \frac{\pi}{2} \right)) = \frac{1}{4} \sin \left[ 3 \left( b + \frac{\pi}{2} \right) \right][/TEX]
[TEX]\Leftrightarrow \cos \left( b \right) \left(-\cos(\frac{\pi}{3} - b) \right) \cos (\frac{\pi}{3} + b) = \frac{1}{4} \sin \left[ 3b+\frac{3\pi}{2} \right][/TEX]
[TEX]\Leftrightarrow-\cos \left( b \right) \cos\left(\frac{\pi}{3} - b \right) \cos \left( \frac{\pi}{3} + b \right) = -\frac{1}{4} \cos \left( 3b \right)[/TEX]
[TEX]\Leftrightarrow \cos \left( b \right) \cos\left(\frac{\pi}{3} - b \right) \cos \left( \frac{\pi}{3} + b \right) = \frac{1}{4} \cos \left( 3b \right)[/TEX]
Áp dụng tính :
cos10cos50cos70
cot20cot40cot80
cos(10)cos(50)cos(70) = cos(10)cos(60 - 10)cos(60 + 10) = [tex]\frac{1}{4} \cos (30 ^ \circ) = \frac{\sqrt{3}}{8}[/tex]
cot20cot40cot80 = (cos20cos40cos80)/(sin20sin40sin80) = [tex]\frac{\cos(60 ^ \circ)}{\sin(60 ^ \circ)} = \cot (60 ^ \circ) = \frac{1}{\sqrt{3}}[/tex]
thuy_linh_95 said:
Mấy bài này trong SGK cả mà............................................... .............hic
Bài trên cũng sai chỗ
cos(10)cos(50)cos(70) = cos(10)cos(60 - 10)cos(70 - 10) = \frac{1}{4} \cos (30 ^ \circ) = \frac{\sqrt{3}}{8}
Đã sửa